Water footprint assessment at selected boundaries in Perlis - Ahmad Nadymy Bin Roshdy (School of Environmental Engineering, University Malaysia Perlis, 2016)
This project presents the study on a water footprint assessment at selected boundaries in Perlis especially in crop growing areas. Water footprint is an indicator to reveal water pattern usage and it is measured in terms of the volume of water consumed, evaporated or polluted. The objective of this study was to assess green and blue water footprint at selected boundaries and to estimate the total of green and blue water footprint consumed by crops activities at selected boundaries. There is two types of water footprint assessment will be conducted which is green water footprint and blue water footprint. The methodology in accounting water footprint start with selecting the scheme (boundaries/looping) which is Sungai Pelarit's scheme. Next, the dimension of the canal at that boundaries will be measured to get the value of flow rate as well as the crop growing parameters. Therefore, all the related formula and equation regarding water footprint will be assess to get the final or total volume of water footprint. Besides that, there are certain data act as a reference in accounting water footprint for the example effective rainfall data, crop requirement data, crop water used and many others (According to DID Perlis). Based on the result collected in this assessment, the blue water crop use is 2670 m³/ha while the green water crop use is 7160 m³/ha. In terms of crop water requirement, the value that has been collected is 982.8 mm/year. Therefore, the total water footprint process of growing crops for both green and blue is 983 m³/ha. Thus the total water footprint of growing crops is 983 m³/ton. Result and data was collected and analyse in order to achieve the objectives that had been chosen.